Metakaolin-based Geopolymer Concrete; Synthesis, Development and Characterization - Fouad, Heba (AUC Knowledge Fountain, 2024)
Geopolymers are rendered as an essential sustainable replacement to the widely used Ordinary Portland Cement (OPC) which causes immense carbon dioxide emissions, hence a detrimental impact on society’s health and the environment. Geopolymers are three-dimensional networks of polymerized tetrahedral silicate and aluminate in the form of Q4(4Al), Q4(3Al) and Q4(2Al) which act as the principal binding phase in concrete. Past research has reported the synthesis of geopolymers from different aluminosilicates precursors, their characterization, and their wide range properties. However, previous studies still have not properly investigated effective range of synthesis ratios for a particular source material, optimum curing regimes, short- and long-term properties of paste, mortar and concrete, and finally possible construction applications. This research has focused on the study of kaolin calcination for proper geopolymerization of metakaolin using sodium hydroxide and sodium silicate, development of a guidance design chart that shows range of feasible mixes and the design of geopolymer concrete and the study of its mechanical properties. The design chart is the main contribution of this research and aims at providing a well-established baseline for the synthesis of metakaolin geopolymer. In the first stage, the used kaolin was properly characterized before and after calcination using different spectroscopic techniques including XRD, TGA, FTIR and 27Al and 29Si solid state MAS NMR. It was found that calcination at 750°C for 7 hours results in effective breakage of the hydroxyl group from the kaolin sheets. In the second stage, geopolymer paste was produced at different mixing percentages. A total of 52 mixes were designed and studied. Based on the quantitative analysis of compressive strength and qualitative analysis of setting time and workability, the feasible range for producing a workable geopolymer mix of reasonable strength was highlighted. The 28-day compressive strength of geopolymer paste ranged between 30 to 94 MPa and the workability varied from being very stiff to highly workable depending on the synthesis ratios. The research points out a concern, which was not previously addressed in the literature, the high temperature of geopolymer paste at some synthesis percentages. This requires further investigation for practical handling of the material in construction applications. The stress-strain curves of geopolymer paste showed a brittle behavior and the lowest and highest tangent modulus of elasticity at 7-day was recorded to be 4.4 and 7.3 GPa respectively. 29Si and 27Al MAS NMR analysis detected the presence of tetrahedrally coordinated silicate and aluminate crosslinked in form of Q4(4Al) and Q4(3Al) and thus confirmed the formation of geopolymer gel network. Finally, six geopolymer concrete mixes were developed at specific mixing ratios depending on the developed guidance chart and their mechanical properties were investigated. The studied fresh and mechanical properties include workability, temperature, compressive strength, flexural strength, drying shrinkage, rapid chloride penetration test in addition to chemical resistance in acid (10% hydrochloric acid) and sulfates (saturated magnesium sulfate solution) for a total duration of 4 months. It was concluded that calcined kaolin can be alkaline activated to produce geopolymer concrete of comparable or even advanced mechanical properties at ambient curing temperature. Calcination of kaolin is a primary step that needs to be effectively conducted at the right temperature, duration and rate prior to geopolymerization. The crosslinking of silicate and aluminate species to form geopolymer network depends on the synthesis materials percentages. Research conducted contributed to demonstrating the feasible range of metakaolin, sodium silicate and sodium hydroxide to synthesize geopolymer and clarifying the relationship between the percentages of three component system and the compressive strength development as a first step towards reaching a structure-directed synthesis. Geopolymer concrete exhibited superior mechanical properties and can be used in various construction applications based on the obtained properties.